A review of current practices to increase Chlamydia screening in the community – a consumer‐centred social marketing perspective. (12th January 2015) - Phillipson, Lyn; Gordon, Ross; Telenta, Joanne; Magee, Chris; Janssen, Marty
Abstract: Background: Chlamydia trachomatis is one of the most frequently reported sexually transmitted infections (STI) in Australia, the UK and Europe. Yet, rates of screening for STIs remain low, especially in younger adults. Objective: To assess effectiveness of Chlamydia screening interventions targeting young adults in community‐based settings, describe strategies utilized and assess them according to social marketing benchmark criteria. Search strategy: A systematic review of relevant literature between 2002 and 2012 in Medline, Web of Knowledge, PubMed, Scopus and the Cumulative Index to Nursing and Allied Health was undertaken. Results: Of 18 interventions identified, quality of evidence was low. Proportional screening rates varied, ranging from: 30.9 to 62.5% in educational settings ( n  = 4), 4.8 to 63% in media settings ( n  = 6) and from 5.7 to 44.5% in other settings ( n  = 7). Assessment against benchmark criteria found that interventions incorporating social marketing principles were more likely to achieve positive results, yet few did this comprehensively. Most demonstrated customer orientation and addressed barriers to presenting to a clinic for screening. Only one addressed barriers to presenting for treatment after a positive result. Promotional messages typically focused on providing facts and accessing a testing kit. Risk assessment tools appeared to promote screening among higher risk groups. Few evaluated treatment rates following positive results; therefore, impact of screening on treatment rates remains unknown. Discussion: Future interventions should consider utilizing a comprehensive social marketing approach, using formative research to increase insight and segmentation and tailoring of screening interventions. Easy community access to both screening and treatment should be prioritized.